Creating Marketing Strategy to Develop the Best Child Growth and Development Clinic in Indonesia: Case Study of PT. Klinik Lalita Indonesia - Tawakkal, Ahmad; Gunawan, Benny S. (The Indonesian Journal of Business Administration, 2017)
Abstract: Indonesia population is growing fast. According to Profil Kesehatan Indonesia 2015, there are 4.883.184 new babies born every year. Most of the babies grow healthy, but approximately 13% of them will have some form of growth or development disorder. This disorder will diminish the quality of our future generation if not properly treated. In order to solve this problem, PT. Klinik Lalita Indonesia develop special clinic for child growth and development named Klinik Lalita. In the market, there are several hospitals offering examination and therapy fo child growth and development disorders. With minimum capital, Klinik Lalita must develop effective marketing strategy to compete with hospitals with bigger capital. To develop proper marketing strategy, writer do several analysis: Customer problem, Strategi Canvas, Porter Five Forces Analysis, TOWS Analysis, and 7P Marketing Mix Analysis. From that analysis, writer conclude that the best strategy for Klinik Lalita is Focus Differentiation Strategy. The strategy can be broken down into several points: Focus only on child growth and development services; Maintaining good examination and therapy scheduling; choosing clinic location with strategic access, and Choosing clinic with vast parking space.Keyword : Child growth and development disorders, Klinik Lalita, PT. Klinik Lalita Indonesia